Nickel-plated lead-free tin wire and preparation method thereof
By covering the composite corrosion inhibitor microcapsules on the lead-free tin wire and forming a mesh structure with silicon carbide nanowires, the problem of corrosion of lead-free tin wire when soldering nickel-plated material is solved, and the effect of improving the corrosion resistance and welding effect of the tin wire is achieved.
Patent Information
- Application Number
- CN202510349920.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-24
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2045-03-24
AI Technical Summary
When welding nickel-plated parts, the rosin and additives are unevenly distributed, resulting in corrosion of the welding substrate and affecting the service life.
Compound corrosion inhibitors are used to synthesize quaternary ammonium corrosion inhibitors and embed them with gelatin and chitosan as wall materials. The network structure is formed in combination with silicon carbide nanowires to enhance the strength of the wall material, and porous composite nanosheets are formed through ultrasonic treatment, which are coated on the surface of the tin wire to slow down corrosion.
Effectively reduce the damage caused by corrosion in tin wire, improve corrosion resistance, avoid welding spot corrosion and oxidation, and improve welding effect and service life.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of lead-free tin wire preparation, in particular to a nickel-plated lead-free tin wire and a preparation method thereof. Background Art
[0002] Lead-free tin wire is also called environmentally friendly tin wire. Lead-free tin wire is a solder wire made of lead-free alloy and is used for welding electronic components. Lead-free tin wire is more environmentally friendly than lead tin wire. Lead tin wire will release harmful lead vapor during the welding process, polluting the environment and endangering human health. Lead-free tin wire does not contain harmful lead elements and will not produce harmful lead vapor, making it safer and more environmentally friendly. Due to the improvement of environmental protection requirements, lead-free tin wire has gradually replaced lead tin wire and become the mainstream. Lead-free tin wire is more widely used in the welding of electronic components, especially in the fields of electronic product manufacturing and the electronics industry.
[0003] In order to extend the service life or prevent rust, various electronic product components are now nickel-plated on the surface of the components. Ordinary rosin-type lead-free tin wire cannot wet the surface of the nickel-plated layer, resulting in poor welding effect, low product yield, short service life, and even scrapping. For example, the invention patent with the announcement number CN107127473A discloses a nickel-plated lead-free tin wire, including lead-free solder wire, the lead-free solder wire components include 100-150 parts of tin, 3-11 parts of copper, 0.5-1.5 parts of silver, 0.1-0.4 parts of cobalt, 5-15 parts of rosin and 3-12 parts of additives by weight. The preparation process of the patent is simple. When the prepared solder wire is used to weld stainless steel or nickel-plated parts, the surface of the parts such as stainless steel or nickel-plated materials can be partially corroded, so that the solder joints are firm and reliable; although the nickel-plated lead-free tin wire solves the problem of firm and reliable solder joints, during the welding process, rosin, additives, etc. are splashed onto the welding substrate due to uneven distribution to form residues, and the welding substrate is easily corroded by the welding residues, thereby affecting the use. Summary of the invention
[0004] In view of the problems existing in the prior art, the object of the present invention is to provide a nickel-plated lead-free tin wire and a preparation method thereof.
[0005] To achieve the above object, the present invention provides the following technical solutions: A nickel-plated lead-free tin wire, comprising a lead-free solder wire, wherein the lead-free solder wire components include lead-free solder and flux; The lead-free solder comprises 120-180 parts of tin, 5-10 parts of copper, 0.5-1.3 parts of silver and 0.1-0.6 parts of cobalt in parts by weight; The soldering flux comprises 1-2 parts of organic solvent, 2-3 parts of activator, 0.2-0.7 parts of composite corrosion inhibitor and 3-5 parts of rosin by weight.
[0006] As a further preferred embodiment of the present invention, the organic solvent is one or more of ethylene glycol, propylene glycol methyl ether, and ethylene glycol ethyl ether; The active agent is one or more of glutaric acid, citric acid, and salicylamide; The rosin is one or more of polymerized rosin, disproportionated rosin and hydrogenated rosin.
[0007] As a further preferred embodiment of the present invention, the preparation method of the composite corrosion inhibitor is as follows: 1) Add copper sulfate solution to deionized water, then add polyvinyl pyrrolidone aqueous solution and potassium bromide solution in sequence, stir thoroughly to obtain a precursor solution, then place in a constant temperature water bath at 80-85°C, add ascorbic acid solution to the precursor solution under stirring conditions of 80-130r / min, react for 1-2h, centrifuge the obtained product for 5-10min, purify repeatedly with deionized water and dry to obtain flaky copper micro-nano particles; 2) Add the flaky copper micro-nanoparticles to deionized water, disperse them uniformly by ultrasonication, add the citric acid solution, mix them thoroughly, then add the silver nitrate solution, react at 200-300W at room temperature for 15-30min, after the reaction is completed, centrifuge the obtained product for 5-10min, purify it repeatedly with deionized water and dry it to obtain a porous composite nanosheet; 3) The porous composite nanosheets are dispersed in deionized water to obtain a dispersion, and then silicon carbide nanowires are added. Under 300-500W ultrasonic action, the dispersion is mechanically stirred at 1000-2000r / min for 1-2h, and then placed in a vacuum impregnation tank, and corrosion inhibitor microcapsules are added. The dispersion is evacuated to 100-200Pa, and 100-150W ultrasonic action is applied. After treating for 15-30min, the pressure is released to normal pressure, and the product is centrifuged and dried to obtain a composite corrosion inhibitor.
[0008] As a further preferred embodiment of the present invention, in step 1), the concentration of the copper sulfate solution is 1.0-1.3 mol / L; The concentration of the polyvinyl pyrrolidone aqueous solution is 40-60 g / L; The concentration of the potassium bromide solution is 0.1-0.3 mol / L; The concentration of the ascorbic acid solution is 1.5-1.8 mol / L; The volume ratio of the copper sulfate solution, deionized water, polyvinyl pyrrolidone aqueous solution, potassium bromide solution and ascorbic acid solution is (1-3): (5-15): (2-10): (0.5-2.5): (1-3); The centrifugal speed is 8000-10000r / min.
[0009] As a further preferred embodiment of the present invention, in step 2), the concentration of the citric acid solution is 0.1-0.2 mol / L; The concentration of the silver nitrate solution is 0.2-0.3 mol / L; The usage ratio of the flaky copper micro-nano particles, deionized water, citric acid solution, and silver nitrate solution is (0.3-0.7) g: (8-12) mL: (0.1-0.2) mL: (0.5-0.8) mL; The centrifugal speed is 8000-10000r / min.
[0010] As a further preferred embodiment of the present invention, in step 3), the usage ratio of the porous composite nanosheets, deionized water, silicon carbide nanowires, and corrosion inhibitor microcapsules is (5-10) g: (120-200) mL: (2-3) g: (3-6) g.
[0011] As a further preferred embodiment of the present invention, the preparation method of the corrosion inhibitor microcapsule is as follows: 1) Place lauric acid, xylene and diethylenetriamine in a container, heat to 170-175°C, react for 3-5 hours, then heat to 210-216°C, continue to react for 3-5 hours, after the reaction is completed, cool to room temperature under vacuum conditions, perform reduced pressure distillation and cool to room temperature to obtain an intermediate, then add benzyl chloride, react at 80-85°C for 3-5 hours under stirring, and then decolorize and recrystallize to obtain a corrosion inhibitor; 2) Dissolve 1.2-2.0 g of gelatin in 50-80 mL of deionized water, heat to 55-60° C. to completely dissolve it to obtain a gelatin solution, then add 0.3-0.7 g of silicon carbide nanowires and 1.2-2.0 g of chitosan to 50-80 mL of deionized water, stir thoroughly, and then dropwise add to the gelatin solution. After mixing evenly, add acetic acid solution to adjust the pH value to 4.0-4.5, add 0.5-1.2 g of corrosion inhibitor, stir thoroughly for 1-2 hours, and then add 2-3 drops of glutaraldehyde. After the corrosion inhibitor is encapsulated in the microcapsule, dry it, and obtain the corrosion inhibitor microcapsule.
[0012] As a further preferred embodiment of the present invention, in step 1), the usage ratio of lauric acid, xylene, diethylenetriamine and benzyl chloride is (40-60) g: (40-60) mL: (24-36) mL: (25-38) mL.
[0013] As a further preferred embodiment of the present invention, in step 2), the concentration of the acetic acid solution is 36-38 wt %.
[0014] A method for preparing a nickel-plated lead-free tin wire specifically comprises the following steps: 1) Mix copper, silver and cobalt, add them into a heating container, heat them into a fluid, and mix them evenly to obtain a premix; 2) Add tin to the premix, mix and then use the method of pouring, extruding and drawing to obtain a semi-finished tin wire; 3) Add organic solvent, activator and rosin into the container, dissolve and stir at 150-165℃ until it becomes liquid, then add composite corrosion inhibitor, stir thoroughly, extrude and mix with semi-finished tin wire, and then go through wire drawing process to get the required lead-free tin wire.
[0015] Compared with the prior art, the present invention has the following beneficial effects: In the present invention, lauric acid, diethylenetriamine and benzyl chloride are used as raw materials to synthesize a quaternary ammonium salt corrosion inhibitor, and then a re-coagulation method is adopted to embed the corrosion inhibitor with gelatin and chitosan as wall materials, so as to obtain a microcapsule corrosion inhibitor. When the tin wire is corroded, the microcapsule corrosion inhibitor is ruptured in response to external corrosion, and the coated corrosion inhibitor is released, thereby slowing down the corrosion damage of the tin wire and improving the corrosion resistance of the tin wire. In addition, silicon carbide nanowires are added to the wall material of the microcapsule corrosion inhibitor. During the stirring process, the silicon carbide nanowires are entangled with each other to form a mesh structure, thereby playing a role in transmitting and dispersing stress in the wall material, and enhancing the wall material. The strength of the microcapsule corrosion inhibitor is such that the formed microcapsule corrosion inhibitor has a certain resistance to external forces; at the same time, in the present invention, copper sulfate is used as a copper source, and a liquid phase reduction method is adopted to prepare polygonal flaky copper micro-nano particles with a two-dimensional structure in an aqueous phase, and then the flaky copper micro-nano particles are used as a copper source, and a simple and efficient replacement method is adopted to prepare a porous composite nanosheet with a two-dimensional structure under the action of ultrasound at room temperature, and then the porous composite nanosheet is fully mixed with the silicon carbide nanowire by mechanical stirring under the action of ultrasound, and the silicon carbide nanowire is embedded in the pores of the porous composite nanosheet, and is constructed by cross-linking to form countless independent The mesh structure connects several porous composite nanosheets to form an irregular semi-enclosed body. The microcapsule corrosion inhibitor can be infiltrated into the semi-enclosed body of the construction process by vacuum impregnation. The ultrasonic effect applied can promote the porous composite nanosheets to approach each other and reduce the volume of the semi-enclosed body. At the same time, it can also promote the microcapsule corrosion inhibitor to better penetrate into the semi-enclosed body, so that the microcapsule corrosion inhibitor can be gathered in the semi-enclosed body and fit closely to each other, and it is not easy to overflow from the semi-enclosed body, thereby obtaining a composite corrosion inhibitor with a stable structure; by fully mixing the composite corrosion inhibitor with an organic solvent, an active agent, and rosin Finally, it is coated on the surface of the tin wire to obtain a finished lead-free tin wire. When the lead-free tin wire is used to weld nickel-plated parts, the microcapsule corrosion inhibitor in the composite corrosion inhibitor is ruptured by heat and the corrosion inhibitor is released, which can slow down the corrosion rate of the welding residue on the base material, thereby improving the surface insulation resistance effect. At the same time, the semi-enclosed body in the composite corrosion inhibitor collapses with the rupture of the microcapsule sustained-release agent and recovers to a porous composite nanosheet. These nanosheets can cover the welding point position, play a role in blocking the erosion of external substances, and avoid corrosion and oxidation of the welding point, thereby improving the welding effect and the stability and durability after welding.
[0016] The lead-free tin wire of the present invention has an organic solvent that can make the activator and the composite corrosion inhibitor evenly distributed in the rosin, thereby preventing the activator from splashing onto the welding substrate due to uneven distribution during the welding process of nickel-plated parts, thereby reducing the corrosion of the welding substrate by welding residues. At the same time, the microcapsule corrosion inhibitor in the composite corrosion inhibitor is ruptured by heat to release the corrosion inhibitor, which can slow down the corrosion rate of the welding residue on the substrate material, thereby improving the surface insulation resistance effect. At the same time, the semi-enclosed body in the composite corrosion inhibitor can cover the welding point position after the structure collapses, thereby blocking the erosion of external substances, avoiding corrosion and oxidation of the welding point, thereby improving the welding effect and the stability and durability after welding. DETAILED DESCRIPTION
[0017] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0018] In the embodiment of the present invention, the organic solvent is ethylene glycol; the activator is glutaric acid; and the rosin is hydrogenated rosin.
[0019] Embodiment 1: A nickel-plated lead-free tin wire, comprising a lead-free solder wire, wherein the lead-free solder wire components include lead-free solder and flux; Among them, lead-free solder includes 120 parts of tin, 5 parts of copper, 0.5 parts of silver and 0.1 parts of cobalt by weight; The soldering flux comprises, by weight, 1 part of an organic solvent, 2 parts of an activator, 0.2 parts of a composite corrosion inhibitor and 3 parts of rosin.
[0020] The preparation method of the nickel-plated lead-free tin wire specifically comprises the following steps: 1) Mix copper, silver and cobalt, add them into a heating container, heat them into a fluid, and mix them evenly to obtain a premix; 2) Add tin to the premix, mix and then use the method of pouring, extruding and drawing to obtain a semi-finished tin wire; 3) Add organic solvent, activator and rosin into the container, dissolve and stir at 150°C until it becomes liquid, then add composite corrosion inhibitor, stir thoroughly, extrude and mix with semi-finished tin wire, and then go through wire drawing process to get the required lead-free tin wire.
[0021] The preparation method of the composite corrosion inhibitor is as follows: 1) 40g of lauric acid, 40mL of xylene and 24mL of diethylenetriamine were placed in a container, heated to 170°C, reacted for 3h, then heated to 210°C, and continued to react for 3h. After the reaction was completed, the mixture was cooled to room temperature under vacuum conditions, and then vacuum distilled and cooled to room temperature to obtain an intermediate. Then 25mL of benzyl chloride was added, and the mixture was reacted at 80°C for 3h under stirring. After decolorization and recrystallization, a corrosion inhibitor was obtained. 2) Dissolve 1.2 g of gelatin in 50 mL of deionized water, heat to 55 °C to completely dissolve it, and obtain a gelatin solution. Then, add 0.3 g of silicon carbide nanowires and 1.2 g of chitosan to 50 mL of deionized water, stir thoroughly, and then dropwise add to the gelatin solution. After mixing evenly, add 36 wt% acetic acid solution to adjust the pH value to 4.0, add 0.5 g of corrosion inhibitor, stir thoroughly for 1 hour, and then add 2 drops of glutaraldehyde. After the corrosion inhibitor is encapsulated in the microcapsules, dry and obtain corrosion inhibitor microcapsules. 3) Add 1 mL of 1.0 mol / L copper sulfate solution to 5 mL of deionized water, then add 2 mL of 40 g / L polyvinyl pyrrolidone aqueous solution and 0.5 mL of 0.1 mol / L potassium bromide solution in sequence, stir well to obtain a precursor solution, then place in a constant temperature water bath at 80°C, add 1 mL of 1.5 mol / L ascorbic acid solution to the precursor solution under stirring at 80 r / min, react for 1 h, centrifuge the product at 8000 r / min for 5 min, purify repeatedly with deionized water and dry to obtain flaky copper micro-nanoparticles; 4) Add 0.3g of flaky copper micro-nanoparticles to 8mL of deionized water, disperse them uniformly by ultrasonication, add 0.1mL of 0.1mol / L citric acid solution, mix them thoroughly, then add 0.5mL of 0.2mol / L silver nitrate solution, react at 200W for 15min at room temperature, after the reaction is completed, centrifuge the obtained product at 8000r / min for 5min, purify it repeatedly with deionized water and dry it to obtain a porous composite nanosheet; 5) Disperse 5 g of porous composite nanosheets in 120 mL of deionized water to obtain a dispersion, then add 2 g of silicon carbide nanowires, mechanically stir at 1000 r / min for 1 h under 300 W ultrasonic action, then place in a vacuum impregnation tank, add 3 g of corrosion inhibitor microcapsules, evacuate to 100 Pa, and apply 100 W ultrasonic action. After treating for 15 minutes, release the pressure to normal pressure, centrifuge the product and dry it to obtain a composite corrosion inhibitor.
[0022] Embodiment 2: A nickel-plated lead-free tin wire, comprising a lead-free solder wire, wherein the lead-free solder wire components include lead-free solder and flux; Among them, lead-free solder includes 150 parts of tin, 8 parts of copper, 0.8 parts of silver and 0.3 parts of cobalt by weight; The soldering flux includes 1.5 parts of organic solvent, 2.5 parts of activator, 0.5 parts of composite corrosion inhibitor and 4 parts of rosin by weight.
[0023] The preparation method of the nickel-plated lead-free tin wire specifically comprises the following steps: 1) Mix copper, silver and cobalt, add them into a heating container, heat them into a fluid, and mix them evenly to obtain a premix; 2) Add tin to the premix, mix and then use the method of pouring, extruding and drawing to obtain a semi-finished tin wire; 3) Add organic solvent, activator and rosin into the container, dissolve and stir at 155°C until it becomes liquid, then add composite corrosion inhibitor, stir thoroughly, extrude and mix with semi-finished tin wire, and then go through wire drawing process to get the required lead-free tin wire.
[0024] The preparation method of the composite corrosion inhibitor is as follows: 1) 50g of lauric acid, 50mL of xylene and 30mL of diethylenetriamine were placed in a container, heated to 172°C, reacted for 4 hours, then heated to 215°C, and continued to react for 4 hours. After the reaction was completed, the mixture was cooled to room temperature under vacuum conditions, and then vacuum distilled and cooled to room temperature to obtain an intermediate. Then 30mL of benzyl chloride was added, and the mixture was reacted at 82°C for 4 hours under stirring. After decolorization and recrystallization, a corrosion inhibitor was obtained. 2) Dissolve 1.6 g of gelatin in 70 mL of deionized water, heat to 57 ° C to completely dissolve it, and obtain a gelatin solution. Then, add 0.5 g of silicon carbide nanowires and 1.8 g of chitosan to 70 mL of deionized water, stir thoroughly, and then add dropwise to the gelatin solution. After mixing evenly, add 37 wt% acetic acid solution to adjust the pH value to 4.5, add 0.7 g of corrosion inhibitor, stir thoroughly for 1.5 hours, and then add 3 drops of glutaraldehyde. After the corrosion inhibitor is encapsulated in the microcapsule, it is dried to obtain the corrosion inhibitor microcapsule. 3) Add 2 mL of 1.2 mol / L copper sulfate solution to 10 mL of deionized water, then add 8 mL of 50 g / L polyvinyl pyrrolidone aqueous solution and 1.5 mL of 0.2 mol / L potassium bromide solution in sequence, stir well to obtain a precursor solution, then place in a constant temperature water bath at 83°C, under stirring at 100 r / min, add 2 mL of 1.7 mol / L ascorbic acid solution to the precursor solution, react for 1.5 h, centrifuge the product at 9000 r / min for 8 min, purify repeatedly with deionized water and dry to obtain flaky copper micro-nanoparticles; 4) Add 0.5g of flaky copper micro-nanoparticles to 10mL of deionized water, disperse them uniformly by ultrasonication, add 0.2mL of 0.2mol / L citric acid solution, mix them thoroughly, then add 0.7mL of 0.3mol / L silver nitrate solution, react at 300W for 25min at room temperature, after the reaction is completed, centrifuge the obtained product at 9000r / min for 8min, purify it repeatedly with deionized water and dry it to obtain a porous composite nanosheet; 5) Disperse 7 g of porous composite nanosheets in 160 mL of deionized water to obtain a dispersion, then add 2.5 g of silicon carbide nanowires, mechanically stir at 1500 r / min for 1.5 h under 400 W ultrasonic action, then place in a vacuum impregnation tank, add 5 g of corrosion inhibitor microcapsules, evacuate to 150 Pa, apply 150 W ultrasonic action, treat for 25 min, release the pressure to normal pressure, centrifuge the product and dry it to obtain a composite corrosion inhibitor.
[0025] Embodiment 3: A nickel-plated lead-free tin wire, comprising a lead-free solder wire, wherein the lead-free solder wire comprises lead-free solder and flux; Among them, lead-free solder includes 180 parts of tin, 10 parts of copper, 1.3 parts of silver and 0.6 parts of cobalt by weight; The soldering flux comprises 2 parts of organic solvent, 3 parts of activator, 0.7 parts of composite corrosion inhibitor and 5 parts of rosin by weight.
[0026] The preparation method of the nickel-plated lead-free tin wire specifically comprises the following steps: 1) Mix copper, silver and cobalt, add them into a heating container, heat them into a fluid, and mix them evenly to obtain a premix; 2) Add tin to the premix, mix and then use the method of pouring, extruding and drawing to obtain a semi-finished tin wire; 3) Add organic solvent, activator and rosin into the container, dissolve and stir at 165°C until it becomes liquid, then add the composite corrosion inhibitor, stir thoroughly, extrude and mix with the semi-finished tin wire, and then go through the wire drawing process to obtain the required lead-free tin wire.
[0027] The preparation method of the composite corrosion inhibitor is as follows: 1) 60g of lauric acid, 60mL of xylene and 36mL of diethylenetriamine were placed in a container, heated to 175°C, reacted for 5h, then heated to 216°C, and continued to react for 5h. After the reaction was completed, the mixture was cooled to room temperature under vacuum conditions, and then vacuum distilled and cooled to room temperature to obtain an intermediate. Then 38mL of benzyl chloride was added, and the mixture was reacted at 85°C for 5h under stirring. After decolorization and recrystallization, a corrosion inhibitor was obtained. 2) Dissolve 2.0 g of gelatin in 80 mL of deionized water, heat to 60 ° C to completely dissolve it, and obtain a gelatin solution. Then, add 0.7 g of silicon carbide nanowires and 2.0 g of chitosan to 80 mL of deionized water, stir thoroughly, and then add dropwise to the gelatin solution. After mixing evenly, add 38 wt% acetic acid solution to adjust the pH value to 4.5, add 1.2 g of corrosion inhibitor, stir thoroughly for 2 hours, and then add 3 drops of glutaraldehyde. After the corrosion inhibitor is encapsulated in the microcapsule, it is dried to obtain the corrosion inhibitor microcapsule. 3) Add 3 mL of 1.3 mol / L copper sulfate solution to 15 mL of deionized water, then add 10 mL of 60 g / L polyvinyl pyrrolidone aqueous solution and 2.5 mL of 0.3 mol / L potassium bromide solution in sequence, stir well to obtain a precursor solution, then place in a constant temperature water bath at 85°C, under stirring at 130 r / min, add 3 mL of 1.8 mol / L ascorbic acid solution to the precursor solution, react for 2 h, centrifuge the product at 10000 r / min for 10 min, purify repeatedly with deionized water and dry to obtain flaky copper micro-nanoparticles; 4) 0.7 g of flaky copper micro-nanoparticles were added to 12 mL of deionized water, and after ultrasonic dispersion, 0.2 mL of 0.2 mol / L citric acid solution was added, and after thorough mixing, 0.8 mL of 0.3 mol / L silver nitrate solution was added, and the mixture was reacted at 300 W for 30 min at room temperature. After the reaction was completed, the obtained product was centrifuged at 10,000 r / min for 10 min, and repeatedly purified with deionized water and dried to obtain a porous composite nanosheet; 5) Disperse 10 g of porous composite nanosheets in 200 mL of deionized water to obtain a dispersion, then add 3 g of silicon carbide nanowires, mechanically stir at 2000 r / min for 2 h under 500 W ultrasonic action, then place in a vacuum impregnation tank, add 6 g of corrosion inhibitor microcapsules, evacuate to 200 Pa, and apply 150 W ultrasonic action. After treating for 30 minutes, release the pressure to normal pressure, centrifuge the product and dry it to obtain a composite corrosion inhibitor.
[0028] Comparative Example 1: This comparative example is basically the same as Example 1, except that it does not contain a composite corrosion inhibitor.
[0029] Comparative Example 2: This comparative example is basically the same as Example 1, except that in the preparation of the composite corrosion inhibitor, step 1-2) is omitted.
[0030] Comparative Example 3: This comparative example is basically the same as Example 1, except that step 3) is omitted in the preparation of the composite corrosion inhibitor.
[0031] Comparative Example 4: This comparative example is basically the same as Example 1, except that step 4) is omitted in the preparation of the composite corrosion inhibitor.
[0032] Comparative Example 5: This comparative example is basically the same as Example 1, except that in the preparation of the composite corrosion inhibitor, steps 3-5) are omitted.
[0033] Test experiment: The insulation performance of the lead-free tin wires prepared in the embodiments of the present invention and the comparative examples was tested, and the data obtained are as follows:
[0034] It can be seen from the above table that the lead-free tin wire in the embodiment of the present invention can effectively slow down the corrosion rate of the soldering residue on the base material and avoid corrosion and oxidation of the soldering points, thereby improving the surface insulation resistance effect.
[0035] The preferred embodiments of the present invention disclosed above are only used to help illustrate the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.
Claims
1. A nickel-plated lead-free tin wire, comprising a lead-free solder wire, characterized in that: The lead-free solder wire components include lead-free solder and flux; The lead-free solder comprises 120-180 parts of tin, 5-10 parts of copper, 0.5-1.3 parts of silver and 0.1-0.6 parts of cobalt in parts by weight; The soldering flux comprises 1-2 parts of organic solvent, 2-3 parts of activator, 0.2-0.7 parts of composite corrosion inhibitor and 3-5 parts of rosin by weight.
2. The nickel-plated lead-free tin wire according to claim 1, characterized in that: The organic solvent is one or more of ethylene glycol, propylene glycol methyl ether, and ethylene glycol ethyl ether; The active agent is one or more of glutaric acid, citric acid, and salicylamide; The rosin is one or more of polymerized rosin, disproportionated rosin and hydrogenated rosin.
3. The nickel-plated lead-free tin wire according to claim 1, characterized in that: The preparation method of the composite corrosion inhibitor is as follows: 1) Add copper sulfate solution to deionized water, then add polyvinyl pyrrolidone aqueous solution and potassium bromide solution in sequence, stir thoroughly to obtain a precursor solution, then place in a constant temperature water bath at 80-85°C, add ascorbic acid solution to the precursor solution under stirring conditions of 80-130r / min, react for 1-2h, centrifuge the obtained product for 5-10min, purify repeatedly with deionized water and dry to obtain flaky copper micro-nano particles; 2) Add the flaky copper micro-nanoparticles to deionized water, disperse them uniformly by ultrasonication, add the citric acid solution, mix them thoroughly, then add the silver nitrate solution, react at 200-300W at room temperature for 15-30min, after the reaction is completed, centrifuge the obtained product for 5-10min, purify it repeatedly with deionized water and dry it to obtain a porous composite nanosheet; 3) The porous composite nanosheets are dispersed in deionized water to obtain a dispersion, and then silicon carbide nanowires are added. Under 300-500W ultrasonic action, the dispersion is mechanically stirred at 1000-2000r / min for 1-2h, and then placed in a vacuum impregnation tank, and corrosion inhibitor microcapsules are added. The dispersion is evacuated to 100-200Pa, and 100-150W ultrasonic action is applied. After treating for 15-30min, the pressure is released to normal pressure, and the product is centrifuged and dried to obtain a composite corrosion inhibitor.
4. The nickel-plated lead-free tin wire according to claim 3, characterized in that: In step 1), the concentration of the copper sulfate solution is 1.0-1.3 mol / L; The concentration of the polyvinyl pyrrolidone aqueous solution is 40-60 g / L; The concentration of the potassium bromide solution is 0.1-0.3 mol / L; The concentration of the ascorbic acid solution is 1.5-1.8 mol / L; The volume ratio of the copper sulfate solution, deionized water, polyvinyl pyrrolidone aqueous solution, potassium bromide solution and ascorbic acid solution is (1-3): (5-15): (2-10): (0.5-2.5): (1-3); The centrifugal speed is 8000-10000r / min.
5. The nickel-plated lead-free tin wire according to claim 3, characterized in that: In step 2), the concentration of the citric acid solution is 0.1-0.2 mol / L; The concentration of the silver nitrate solution is 0.2-0.3 mol / L; The usage ratio of the flaky copper micro-nano particles, deionized water, citric acid solution, and silver nitrate solution is (0.3-0.7) g: (8-12) mL: (0.1-0.2) mL: (0.5-0.8) mL; The centrifugal speed is 8000-10000r / min.
6. The nickel-plated lead-free tin wire according to claim 3, characterized in that: In step 3), the usage ratio of the porous composite nanosheet, deionized water, silicon carbide nanowires, and corrosion inhibitor microcapsules is (5-10) g: (120-200) mL: (2-3) g: (3-6) g.
7. The nickel-plated lead-free tin wire according to claim 3, characterized in that: The preparation method of the corrosion inhibitor microcapsule is as follows: 1) Place lauric acid, xylene and diethylenetriamine in a container, heat to 170-175°C, react for 3-5 hours, then heat to 210-216°C, continue to react for 3-5 hours, after the reaction is completed, cool to room temperature under vacuum conditions, perform reduced pressure distillation and cool to room temperature to obtain an intermediate, then add benzyl chloride, react at 80-85°C for 3-5 hours under stirring, and then decolorize and recrystallize to obtain a corrosion inhibitor; 2) Dissolve 1.2-2.0 g of gelatin in 50-80 mL of deionized water, heat to 55-60° C. to completely dissolve it, and obtain a gelatin solution. Add 0.3-0.7 g of silicon carbide nanowires and 1.2-2.0 g of chitosan to 50-80 mL of deionized water, stir thoroughly, and then dropwise add to the gelatin solution. After mixing evenly, add acetic acid solution to adjust the pH value to 4.0-4.5, add 0.5-1.2 g of corrosion inhibitor, stir thoroughly for 1-2 hours, and then add 2-3 drops of glutaraldehyde. After the corrosion inhibitor is encapsulated in the microcapsules, dry the microcapsules, and obtain corrosion inhibitor microcapsules.
8. The nickel-plated lead-free tin wire according to claim 7, characterized in that: In step 1), the usage ratio of lauric acid, xylene, diethylenetriamine and benzyl chloride is (40-60) g: (40-60) mL: (24-36) mL: (25-38) mL.
9. The nickel-plated lead-free tin wire according to claim 7, characterized in that: In step 2), the concentration of the acetic acid solution is 36-38 wt %.
10. A method for preparing a nickel-plated lead-free tin wire according to any one of claims 1 to 9, characterized in that: The specific steps include: 1) Mix copper, silver and cobalt, add them into a heating container, heat them into a fluid, and mix them evenly to obtain a premix; 2) Add tin to the premix, mix and then use the method of pouring, extruding and drawing to obtain a semi-finished tin wire; 3) Add organic solvent, activator and rosin into the container, dissolve and stir at 150-165℃ until it becomes liquid, then add composite corrosion inhibitor, stir thoroughly, extrude and mix with semi-finished tin wire, and then go through wire drawing process to get the required lead-free tin wire.
Citation Information
Patent Citations
Composition comprising particulate zinc material with a high relative zinc lability
CN101151067A
Nickel-plated lead-free tin wire
CN107127473A
Lead-free solder tin wire applicable to drag soldering technology
CN107498208A
Lead-free anti-oxidation tin paste and preparation method thereof
CN109955001A
Metal slow-release additive suitable for whole environment and preparation method of metal slow-release additive
CN111607795A